A novel route to process rationalisation on cellulose dyeing - Pervez Md. Nahid; Hoque Mohammed Akramul; Yu Liping; Rinkon Md. Moshfique Hossain; Amin Md. Salman; Ehsan Md. Nazmul; Cai Yingjie (MATEC Web of Conferences, 2017)
This research work presents an altercation on dyeing machine controlling parameters, particularly in terms of the relation between the effect of different factors i.e. reel speed (m min−1), cycle time (min), pump pressure (%) and nozzle position (%) on color strength (K/S) property of different type’s cotton fabric, so only the process controlling parameters were varied; the material used for the study remained the aforementioned throughout. The optimum reel speed, cycle time, pump pressure and nozzle position were found to be 240 m min−1, 2.5 min, 60% and 70% respectively for winch dyeing machine with respect to cellulose materials. This work is useful in selecting optimum values of various controlling parameters that would not alone approve the process rationalisation but as well reduce the fabric consumption and advance the superior of the dyed fabric on applied imminence.